Criminal Tax Law Strategy Regarding Fictitious Tax Invoices for Business Sustainability - Nathan Thomas; Nourma Dewi; Firstnandiar Glica Aini Suniaprily (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
This study aims to examine criminal tax law provisions in Indonesia relating to the issuance of fictitious tax invoices, as well as to analyze criminal law enforcement strategies applicable to cases of fictitious tax invoices at PT PP. A fictitious tax invoice is an invoice issued without any actual transaction to reduce tax liabilities. This research is a normative study using a case and statistical approaches. The results show that the Indonesian taxation system, such as VAT, adopts a self-assessment system that is exploited for fraud, including fictitious tax invoices, as happened to PT PP. As a result, the DGT issued a warning, deactivated access to tax invoice creation, and is potentially subject to administrative sanctions in the form of a 100% increase in unpaid VAT in accordance with Article 15 paragraph (2) of the KUP Law. In addition to administrative sanctions, the issuance and/or use of fictitious tax invoices based on Article 39A of the KUP Law is punishable by a maximum imprisonment of 6 years and a maximum fine of 6 times the amount of tax in the tax invoice.